The Genetic Toxicity of Polycyclic Aromatic Hydrocarbons: A Cross-Tissue, Multi-Endpoint Study in the Transgenic MutaMouse - Long, Alexandra (Université d'Ottawa / University of Ottawa, 2017)
Polycyclic aromatic hydrocarbons (PAHs) are produced via the incomplete combustion of organic matter. They are ubiquitously present in the environment, and human exposures typically involve complex PAH mixtures in complex matrices (e.g., soil, urban air). Many PAHs are genotoxic carcinogens; exposures can augment cancer risk and reliable risk assessment of PAH mixtures is a regulatory concern. There is a paucity of in vivo genotoxicity information for most PAHs and PAH mixtures. Risk assessment of PAH mixtures assumes dose addition (i.e., additive, incremental contributions from each PAH); however, there is a lack of evidence to support this assumption. This thesis assessed the in vivo genotoxicity of 9 PAHs and 6 PAH mixtures following sub-chronic oral exposure of transgenic Muta™Mouse (i.e., adduct and lacZ mutant frequency across 5 tissues). The results revealed that PAHs and PAH mixtures induce significant levels of genetic damage; the mixtures induced very high levels of damage and mutations. Differences in the nature and magnitude of the effects in individual tissues appear to be related to the processes that govern PAH metabolism and the processing of genetic damage (e.g., repair and translesion synthesis). Scrutiny of the dose addition assumption revealed more-than-additive effects in tissues proximal to the exposure route (i.e., intestine, liver), but less-than-additive effects in distal tissues (i.e., bone marrow); however, discrepancies between the experimentally-observed and predicted responses were typically small (i.e., within 5-fold). Comparisons of cross-tissue patterns in adduct and mutant frequencies revealed that the frequency of the former is generally inversely related to that of the latter. This appears to be related to the experimental design, and the influence of repair and replication on adduct and mutant frequency. The BMD approach was employed to estimate genotoxic (i.e., adduct) potency and mutagenic (i.e., lacZ mutant) potency for all agent-tissue combinations. The results demonstrate that the mutagenic potency of PAHs and PAH mixtures is empirically related to genotoxic potency; moreover, that there is cross-tissue and cross-compound congruence in the processing of PAH-induced damage. The results obtained significantly advance existing knowledge regarding the genotoxic hazards of PAHs and PAH mixtures; moreover, the empirical relationships between genetic toxicity endpoints.
Keywords: Genetic toxicology; Mutation; Polycyclic aromatic hydrocarbon; Benchmark dose modelling; DNA adduct; Chromosome damage